Implementation of an Efficient Scheme for Dynamic Channel Allocation Using Intelligent Agent in Mobile Communication - Khandare, Swati M.; Sedamkar, R. R. (Novel Perspectives of Engineering Research Vol. 2, 2021)
The demand for mobile communication is steadily increasing. One of the most crucial concerns in the next generation of mobile communication is resource flexibility. To deal with new services and adopt new traffic profiles and characteristics, several strategies are required to boost the network's efficiency and flexibility. Efficiency of channel allocation is an important aspect in mobile communication. The goal of this research is to present a distributed dynamic channel allocation scheme that uses intelligent agents to improve network efficiency and flexibility. Under moderate and heavy load situations, this channel allocation scheme will provide an efficient solution. The agent architecture employed gives base stations greater autonomy and a technique for permitting co-operation and negotiation between them; this autonomy and co-operation allows the network to be more flexible in dealing with new traffic circumstances while also increasing the network's overall robustness. We compared the performance of the Distributed FCA and DCA schemes and discovered that the average call dropping probability of the FCA scheme is 96 percent to 98 percent, while the average call dropping probability of the DCA scheme is 26 percent to 28 percent in various conditions, indicating that the distributed DCA scheme is more efficient than the FCA scheme.